Characterization of LY3324954 a long-acting glucagon-receptor agonist - William Roell; Tamer Coskun; Teayoun Kim; Libbey O’Farrell; Jennifer A. Martin; Shelly Nason; Jasmin Hernandez-Alamillo; Saidharshana Dhantu; Daniel J. Drucker; Kyle W. Sloop; James P. Steele; Jorge Alsina-Fernandez; et al. (Molecular Metabolism)
Objective: Glucagon is a crucial regulator of glucose and lipid metabolism as well as whole-body energy balance. Thus, modulation of glucagon receptor (GCGR) activity in the context of single-molecule multi-receptor co-agonists has become an emerging therapeutic target against obesity and obesity-associated metabolic dysfunction. To better elucidate the role of GCGR-signaling when paired with incretin receptor signaling or on its own, we developed, LY3324954, a GCGR agonist with improved potency and selectivity as compared to the native glucagon peptide. Methods: LY3324954 was administered to DIO mice, rats, dogs, and monkeys to evaluate pharmacokinetic (PK) profile. Biweekly treatments were conducted in lean and DIO mice to characterize LY3324954-effects on glucose homeostasis and energy balance. Single dose studies were also conducted in liver Gcgr-deficient mice to establish receptor specificity. Results: LY3324954 also exhibited extended PK profile in DIO mice, rats, dogs, and monkeys. When administered every 72 h, LY3324954 treatment stimulated transient glucose and insulin excursions in lean mice. In diet-induced obese mice, LY3324954 treatment stimulates energy expenditure, weight loss, and a reduction of adiposity in a dose-dependent manner. Benefit to whole-body lipid homeostasis was likewise observed in these mice. Conclusions: Taken together, these studies characterize a long-acting and potent GCGR-agonist and its regulation of glucose and lipid metabolism as well as whole-body energy balance following both acute and chronic treatment in mice.